HISTORY, SCOPE, METHODS OF EDUCATION PSYCHOLOGY IN STUDENTS IN THE ELEMENTARY SCHOOL ENVIRONMENT - Cahyani, Tiara Nur; Saputri, Astika Nurhayati; Magdalena, Ina (PROGRES PENDIDIKAN, 2021)
SDN Poris Pelawad 1 is a school located in one of the areas in Tangerang City, precisely in Poris Pelawad Village. Since the covid-19 outbreak, which requires all Indonesian citizens and even all over the world to apply WFH (Work Form Home) where the continuity of teaching and learning is also carried out online (In the Network) using media that we already recognize with the term zoom meeting or other media that saves usage. internet package, so that students in the learning process will produce a good ending. Learning is basically a process of interaction between educators and students, both direct (face-to-face) and indirect (learning activities using learning media in web applications). In the midst of the COVID-19 pandemic, teaching and learning activities are recommended to use an online learning model. The government has also provided assistance to students and educators in an effort to provide a free quota of 50GB every month, the level of the amount of the quota depends on the level of education as well, starting from elementary, junior high, high school to college, why is there a need for differences in the amount of quota distribution. Because each level requires different power, the higher the level of majority education, the more power needs that must be spent to achieve something that is expected. This study used an interview method to one of the teachers of SDN Poris Pelawad 1. The interview was conducted directly / offline by approaching the resource person.